2020
DOI: 10.3389/fpsyg.2020.00485
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Shape, Roughness and Gloss on the Perceived Reflectance of Colored Surfaces

Abstract: This study examined perceptual differentiation of specular from diffuse shading for the recovery of surface color and gloss. In Experiment 1, we parametrically varied the mesoscale relief height of globally planar surfaces, specular sharpness and the orientation of the surface relative to the light source. We obtained psychophysical matches for perceived color saturation and value (HSV), but also considered whether the main effects could be influenced by color space used when transforming data to perceptually-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
34
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(56 citation statements)
references
References 37 publications
13
34
3
1
Order By: Relevance
“…The purpose of Experiment 1 was to extend the findings of the original Honson et al (2020) study to multiple hues. Honson et al (2020) found that there was large variation in perceived saturation and lightness as a function of changes in specular roughness, mesoscopic shape, and orientation of the planar surfaces to the light source—which can profoundly change the way light interacts with and is distributed across a surface. Specular coverage will be greater when orienting the surface at 45° so its normals bisect the angle formed between the illumination and viewing directions.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The purpose of Experiment 1 was to extend the findings of the original Honson et al (2020) study to multiple hues. Honson et al (2020) found that there was large variation in perceived saturation and lightness as a function of changes in specular roughness, mesoscopic shape, and orientation of the planar surfaces to the light source—which can profoundly change the way light interacts with and is distributed across a surface. Specular coverage will be greater when orienting the surface at 45° so its normals bisect the angle formed between the illumination and viewing directions.…”
Section: Methodsmentioning
confidence: 99%
“…We measured perceived lightness and saturation ( Experiment 1 ), perceived gloss ( Experiment 2 ), and perceived specular coverage ( Experiment 3 ) for surfaces rendered across these hue conditions at different levels of relief height, specular roughness, and surface orientation relative to the light source. Given that the findings of Honson et al (2020) may be explained by the inability to disentangle specular content from diffuse shading, we predicted that differences in the pattern of results for perceived lightness and saturation would be observed for blue surfaces but would be similar for red and green surfaces. This difference may be predicted by perceptual biases that exist along the blue/yellow axis that make it difficult for the visual system to disentangle a blue surface hue from the illuminant ( Churma, 1994 ; Pearce et al, 2014 ; Winkler et al, 2015 ; Radonijić et al, 2016 ; Weiss et al, 2017 ; Aston et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations